PERLINDUNGAN HUKUM TERHADAP PIHAK KETIGA SEBAGAI PEMILIK JAMINAN KETIKA TIDAK DILAKSANAKANNYA PRINSIP KEHATI -HATIAN OLEH BANK DALAM PERJANJIAN KREDIT DENGAN MEMAKAI JAMINAN - Sugiyono, Heru (Jurnal Yuridis, 2017)
At the present time many cases of violations (non-performance) prudential principles that occur in national banks, one of which brings the impact of loss to third-party insurance as the owner of the object that was never guarantee or give permission to others to pledge land own to a bank. Precautionary principle should be applied by the banks especially in terms of loan disbursements through accurate and in-depth analysis, the proper distribution, control and monitoring of good, valid agreement and meet the requirements of law, binding strong collateral and loan documentation and complete a regular basis.